Good Corporate Governance on Stock Liquidity with Earnings Quality as an Intervening Variable - MARISTIANA AYU (International Journal of Economics, Business, and Entrepreneurship, 2025)
ABSTRACT Good corporate governance also has a good impact as a consideration for investment decisions for investors. The study aims to find empirical evidence of the role of earnings quality as a mediator between corporate governance(GCG) and stock liquidity, with samples of large-capitalization companies and small and medium-capitalizationcompanies. The results of the study prove that corporate governance has a direct effect on stock liquidity, corporate governance has an effect on profit quality both measured by accrual quality and profit predictability, profit qualitymeasured by accrual quality does not affect stock liquidity, but measured by profit predictability has an effect andcorporate governance mediated by profit quality measured by accrual quality has an effect on stock liquidity, butmeasured by profit predictability indirectly cannot provide an effect. The conclusion that corporate governance (GCG) is indirectly mediated by earnings quality is useful for investors, especially in controlling managers to reduce the occurrence of agency problems and reduce the high level ofrisk in investing, which will ultimately increase stock liquidity in the capital market